3D bioprinting: a step forward in creating engineered human tissues and organs - Alheib, O. (2021)
The most remarkable attractiveness of tissue engineering technology relies on its capability of regenerating patients’ tissues and organs by using their own cells, minimizing the shortage of donor organs, and eliminating all the problems related to transplanted organs and their immune rejection. Traditionally, a suitable biomaterial is selected to engineer a temporary platform (scaffold) ready to host living cells and provoke their biological responses. Accordingly, stem cells or progenitor cells are carefully selected, combined with proper growth factors toward building a viable and functional tissue. Although numerous types of engineered tissues have been fabricated successfully, most of the constructs are incapable of mimicking the native tissue and promoting the desired cellular response, due to their poorly designed micro/macrostructure, which will negatively impact their cellular response toward building de novo tissues. Driven by the increasing demand for finding new approaches to create tissues or organs with enhanced complexity, 3D bioprinting has recently emerged as a promising technique to recapitulate cell-to-cell communication and normal functions of living tissues in 3D culture environment. This technology relies on a combination of living cells suspended in an appropriate biomaterial (ink), which as a whole (bioink) is successively deposited in multiple layers to construct the desired 3D structure. This chapter describes the most common 3D bioprinting techniques used in tissue engineering applications. Special attention will be given to the methods that allow to extrude bioinks to precisely build up organ-like models. In addition, the bioinks used to create three-dimensional tissue constructs will be also highlighted. To be more comprehensive, this chapter will also cover most recent bioprinted tissues, organs, and consequently their technical challenges.